Relationship between depressive symptoms and acute low back pain at first medical consultation, three and six weeks of primary care - Elfering, A.; Käser, A.; Melloh, Markus (2014)
Background: Aim of the study was to test lagged reciprocal effects of depressive symptoms and acute low back pain (LBP) across the first weeks of primary care. Methods: In a prospective inception cohort study, 221 primary care patients with acute or subacute LBP were assessed at the time of initial consultation and then followed up at three and six weeks. Key measures were depressive symptoms (modified Zung Self-Rating Depression Scale) and LBP (sensory pain, present pain index and visual analogue scale of the Short-Form McGill Pain Questionnaire). Results: When only cross-lagged effects of six weeks were tested, a reciprocal positive relationship between LBP and depressive symptoms was shown in a cross-lagged structural equation model (ß =.15 and.17, p <.01). When lagged reciprocal paths at three-and six-week follow-up were tested, depressive symptoms at the time of consultation predicted higher LBP severity after three weeks (ß =.23, p <.01). LBP after three weeks had in turn a positive cross-lagged effect on depression after six weeks (ß =.27, p <.001). Conclusions: Reciprocal effects of depressive symptoms and LBP seem to depend on time under medical treatment. Health practitioners should screen for and treat depressive symptoms at the first consultation to improve the LBP treatment. © 2013 Taylor and Francis.